Public perspectives on disinvestments in drug funding: results from a Canadian deliberative public engagement event on cancer drugs - Sarah Costa; Colene Bentley; Dean A. Regier; Helen McTaggart-Cowan; Craig Mitton; Michael M. Burgess; Stuart J. Peacock (BMC Public Health, 2019)
Abstract Background Decisions relating to the funding of new drugs are becoming increasingly challenging due to a combination of aging populations, rapidly increasing list prices, and greater numbers of drug-indication pairs being brought to market. This is especially true in cancer, where rapid list price inflation is coupled with steeply rising numbers of incident cancer cases. Within a publicly funded health care system, there is increasing recognition that resource allocation decisions should consider the reassessment of, and potential disinvestment from, currently funded interventions alongside new investments. Public input into the decision-making process can help legitimize the outcomes and ensure priority-setting processes are aligned with public priorities. Methods In September 2014, a public deliberation event was held in Vancouver, Canada, to obtain public input on the topic of cancer drug funding. Twenty-four members of the general public were tasked with making collective recommendations for policy-makers about the principles that should guide funding decisions for cancer drugs in the province of British Columbia. Deliberative questions and decision aids were used to elicit individuals’ willingness to make trade-offs between expenditures and health outcomes. Results Participants discussed the implications of disinvestment decisions from cancer drugs in terms of its impact on patient choice, fairness and quality of life. Their discussions indicate that in order for a decision to disinvest from currently-funded cancer drugs to be acceptable, it must align with three main principles: the decision must be accompanied by significant gains, described both in terms of cost savings and opportunities to re-invest elsewhere in the health care system; those who are currently prescribed a cancer drug should be allowed to continue their course of treatment (referred to as a continuance clause, or “grandfathering” approach); and it must consider how access to care for specialized populations is impacted. Conclusions The results from this deliberation event provide insight into what is acceptable to British Columbians with respect to disinvestment decisions for cancer drugs. These recommendations can be considered within wider health system decision-making frameworks for funding decisions relating to all drugs, as well as for cancer drugs.